Comparison of graft-versus-host disease-free, relapse-free survival of transplantation using matched sibling donor, matched unrelated donor or unrelated cord blood after myeloablative conditioning for adult patients with hematological malignancies. Issue 9 (1st September 2016) - Konuma, Takaaki; Kato, Seiko; Oiwa-Monna, Maki; Ishii, Hiroto; Tojo, Arinobu; Takahashi, Satoshi
Abstract: The novel composite endpoint of graft-versus-host disease/relapse-free survival (GRFS) was proposed to evaluate ideal healthy recovery without ongoing morbidity in patients undergoing allogeneic hematopoietic cell transplantation (HCT). We herein analyzed long-term GRFS based on the data of 256 patients with hematological malignancies who underwent allogeneic HCT after myeloablative conditioning. The probabilities of GRFS in the entire cohort were 60.1% at 1 year, and 48.6% at 5 years. Compared with unrelated cord blood, the probability of treatment failure as defined by GRFS at 5 years was similar with matched sibling donor (hazard ratio [HR]: 1.33; p  = 0.28), but was significantly higher with matched unrelated donor (HR: 1.96; p  = 0.01) in multivariate analysis. Unrelated cord blood achieved the highest proportion of patients who had not experienced any GRFS events at 5 years. These data suggest that long-term GRFS after HCT was similar in matched sibling donor recipients to unrelated cord blood recipients.